Robotic‐assisted laparoscopic management of renal tumors in children: Preliminary results. (28th May 2019) - Blanc, Thomas; Pio, Luca; Clermidi, Pauline; Muller, Cecile; Orbach, Daniel; Minard‐Colin, Veronique; Harte, Caroline; Meignan, Pierre; Kohaut, Jules; Heloury, Yves; Sarnacki, Sabine
Abstract: Aim: We present the preliminary results of robotic‐assisted laparoscopic (RAL) total and partial nephrectomy for renal malignant tumors in children. Methods: This is a prospective study of patients operated with RAL between December 2016 and September 2018. Patients with Wilms tumors were treated according to the SIOP‐2001 protocol. Patient and tumor characteristics, type of surgery, surgical‐related morbidity, and oncologic outcomes were recorded. Results were compared with a series of patients with similar age‐ and tumor‐related characteristics operated during the same period by an open surgical approach. Results: Ten children underwent RAL nephrectomy with a mean age of five years (3.2–14.1 years). Total nephrectomy was done in six cases for Wilms tumor and in one case for renal sarcoma; three cases were converted. Complete removal of tumor without rupture was achieved in all cases. Postoperative course was uneventful, and patients were discharged between days 2 and 7. Neither recurrence nor medium‐term complications occurred. Nine patients are alive with a median follow‐up of 16 months (6–27 months) and one female died from complications of central nervous system metastases one year after surgery. When compared with the open surgical approach group, median tumor volume was smaller ( P = 0.005), hospital stay was shorter ( P = 0.01), and operative time was similar ( P = 0.20). Conclusions: RAL total and partial nephrectomy procedure for renal tumor in children may be an option in carefully selected cases. Indication should be discussed at tumor boards and surgery performed while adhering strictly to oncological surgical rules.